Tuberculosis drug resistance in Canada: 2006—2016 - Gallant, V (Can Commun Dis Rep, 2017)
BACKGROUND: Drug-resistant strains of tuberculosis (TB) pose a serious threat to TB prevention and control efforts. The Canadian Tuberculosis Laboratory Surveillance System (CTBLSS) was created in 1998 to monitor emerging trends and patterns in TB drug resistance in Canada. OBJECTIVE: To present a descriptive overview of TB drug resistance data collected through the CTBLSS for the years 2006 to 2016 in Canada, with a focus on 2016. METHODS: The CTBLSS is an isolate-based surveillance system designed to collect data on TB drug resistance across Canada. Each year, data are collected and analyzed by the Public Health Agency of Canada (PHAC) and then validated by the submitting laboratory. RESULTS: In 2016, anti-tuberculosis drug susceptibility test results were reported for 1,452 isolates. The proportion of TB drug-resistant strains remained relatively stable with 108 (7.4%) of the isolates classified as monoresistant, five (0.3%) isolates as polyresistant and 17 (1.2%) as multidrug-resistant TB (MDR-TB) strains. In 2016, there were no extensively drug-resistant TB (XDR-TB) isolates identified. Males accounted for 792 (54.5%) of all reported isolates and 64 (49.2%) of the resistant strains and females accounted for 11 (64.7%) of the MDR-TB strains. Between 2006 and 2016, individuals between 15 and 44 years of age comprised 47.4% of all reported isolates, 54.0% of isolates showing any resistance and 72.3% of MDR-TB strains. CONCLUSION: TB drug resistance levels have been relatively low and stable over the past 11 years and have remained below the global average since national surveillance began. However, with growing worldwide concern about drug resistance and the emergence of XDR-TB, the CTBLSS will remain vital to the monitoring of TB drug resistance in Canada.